Young people's self-meaning making through entrepreneurship in Poland, Slovenia and the UK - Balas Rant, Melita (Economic and business review, 2021)
The objective of the paper is to explore young people's motives for pursuing entrepreneurial opportunities instead of a professional career in the public sector or a corporation. As young people increasingly consider alternatives to a traditional career, it is useful to understand what lies behind their entrepreneurial career choice in order to advise small and medium-sized enterprises (SMEs) how to attract a young workforce. A qualitative study consisting of 16 in-depth, semi-structured interviews with young entrepreneurs in Poland, Slovenia and the United Kingdom (UK) identifies a variety of internal and external factors influencing the entrepreneurs' career decisions that were found to be largely homogenous across different countries and contexts. These influences operate at micro, mezzo and macro levels. The findings are explained through Kegan's theory of self-meaning making as well as the SME context and particularities, providing an understanding of what attracts and deters young people facing career choices.
Keywords: contract labour; employment; labour market; majhna in srednja podjetja; pogodbeno delo; SMEs; trg dela; zaposlovanje